2009
DOI: 10.1213/ane.0b013e31818ffc9d
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Xenon Anesthesia on the Relationship Between Cerebral Glucose Metabolism and Blood Flow in Healthy Subjects: A Positron Emission Tomography Study

Abstract: In general, the magnitude of the decreases in rCMR(glc) during 1 minimum alveolar anesthetic concentration xenon anesthesia exceeded the reductions in rCBF. As a result, the ratio between rCMR(glc) and rCBF was shifted to a higher level. Interestingly, xenon-induced changes in cerebral metabolism and blood flow resemble those induced by volatile anesthetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 42 publications
(54 reference statements)
1
15
0
Order By: Relevance
“…This may result in inappropriate luxury perfusion, which should be avoided, particularly in pathological conditions where cerebral homeostasis is already compromised. In addition, increases in GMR caused by anaesthetics are considered harmful . A study compared the relative effects of sevoflurane and propofol anaesthesia on rGMR in humans.…”
mentioning
confidence: 99%
“…This may result in inappropriate luxury perfusion, which should be avoided, particularly in pathological conditions where cerebral homeostasis is already compromised. In addition, increases in GMR caused by anaesthetics are considered harmful . A study compared the relative effects of sevoflurane and propofol anaesthesia on rGMR in humans.…”
mentioning
confidence: 99%
“…This effect is in accordance with the knowledge that medetomidine causes no dose‐dependent insulin suppression and therefore increases glucose levels in dogs . Moreover, results from some human studies have suggested that the relationship between cerebral glucose metabolism and blood flow can be altered by some anesthetics . We have not found any reports examining medetomidine or butorphanol influence on cerebral glucose metabolism and blood flow coupling.…”
Section: Discussionmentioning
confidence: 56%
“…However, with exceptions beginning to emerge (26,27), such studies involve animals under general anesthesia. Anesthesia is well known to cause substantial fluctuations in radiotracer uptake through alterations in delivery (cerebral blood flow) and brain metabolism, suggesting that studies performed under anesthesia are only rough guides for the clinical studies to follow (23,28). Non-human primate studies are expensive, laborious, and not amenable to large sample sizes.…”
Section: Discussionmentioning
confidence: 99%